Website pada Industri Penyiaran Radio di Indonesia: Live Streaming dan Podcasting - Harliantara, Harliantara (Jurnal Studi Komunikasi, 2019)
Radio broadcasting institutions continue to develop with the process of developing transmission technology and audio applications. Any situation in changes in radio technology always adapts in an effort to maximise performance in management. This study uses a qualitative approach that is still not widely done to review the websites of private radio broadcasters with the technique of collecting data through field observations, interviews, and documentation studies. The process is carried out with data analysis techniques by performing 3 (three) aspects of the analysis systematically, namely data reduction, data display, and drawing conclusions. This study found that radio broadcasting in addition to air or broadcast transmission in the form of sound or sound also distributes broadcasts through live streaming or streaming podcasts on the internet (network) in the form of sound, text, images and videos.